Significance of Renewable Energy for Empowering Cooperative-Farming Sector in Majuli Island of India. Issue 1 (January 2021) - Athira, R; Parida, A.; Choudhury, S.
Abstract: Agriculture is the backbone of the Indian economy and plays a vital role in the overall development of the country. Many studies and practices have proved the importance and benefits of electricity in agriculture throughout the world. However, the fossil fuel-based conventional energy supply to agriculture is always associated with environmental issues. In an attempt to study the significance of renewable energy in the cooperative farming sector particularly in the biodiversity regions, Majuli Island of Assam, India has been selected for the case study. Even though the major income source in the said locality is agricultural farming, they are deprived of getting the optimum benefit from this indigenous income source due to lack of technological intervention. Technological intervention in this sector in the biodiversity region is not imaginable without exploring the feasible intervention of renewable energy at an affordable energy cost. Therefore, in this paper, the significance of renewable energy in agriculture considering the environmental issues has been highlighted in general and in cooperative farming in particular.